An overview of the pharmacovigilance system in India. (2nd January 2016) - Mittal, Niti; Mittal, Rakesh; Gupta, M. C.
Abstract: Pharmacovigilance (PV) has witnessed several advancements throughout the world over the past few decades. This review provides an overview of the PV system in India, focusing on the current scenario, its development, the challenges faced, and the interventions suggested for its improvement. The Pharmacovigilance Program of India (PvPI) is playing a major role in gathering drug safety related data and adding it to the WHO database. PvPI fulfills the minimum requirements given by the WHO for any functional national Pharmacovigilance system. The Indian Pharmacopoeia Commission (IPC) is the national coordinating center under PvPI. PV in India relies mainly upon the spontaneous reporting of adverse drug events. The major challenge for PV in India is under-reporting. However, there is an improvement in the number of submitted reports after regular training and awareness programmes, which have been conducted by the IPC. The regular and periodic circulation of the 'PvPI Newsletter' by the IPC has also been instrumental in increasing awareness about PV amongst healthcare professionals and patients. The intensification of PV activities in India demands particular attention in health science curricula. Indeed, a change in mindset is necessary for prescribers, patients, regulatory agencies, and pharmaceutical companies.